MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDESMA) FROM A GOVERNANCE, RISK, COMPLIANCE (GRC) PERSPECTIVE IN LICIN SUBDISTRICT, BANYUWANGI REGENCY - Tengku Melinda; Izzato Millati (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
This study examines the management of Badan Usaha Milik Desa Bersama (BUM Desa Bersama) through the lens of the Governance, Risk, and Compliance (GRC) framework. As a collaborative institution established by several villages, BUM Desa Bersama aims to optimize local economic potential, foster business sustainability, and improve community welfare. The research focuses on BUM Desa Bersama Licin Mandiri as a case study to explore how governance structures, supervisory mechanisms, risk identification and monitoring, and regulatory compliance are practiced at the village enterprise level. A qualitative approach was employed, utilizing surveys, in-depth interviews, direct observation, and document analysis to gather comprehensive data. Triangulation of sources and theories was applied to ensure the validity and reliability of the findings. The analysis reveals that the implementation of GRC principles significantly contributes to enhancing organizational accountability, operational efficiency, and transparency. In terms of governance, BUM Desa Bersama Licin Mandiri demonstrates participatory decision-making processes and structured supervision involving multiple stakeholders. Risk management is reflected in preventive measures against financial, operational, and reputational risks. Compliance practices are evident through adherence to government regulations, contractual obligations, and internal policies and procedures. The findings suggest that applying the GRC framework strengthens the overall resilience of BUM Desa Bersama by integrating good governance, proactive risk mitigation, and consistent regulatory adherence. This study provides both theoretical insights and practical implications, emphasizing that GRC serves not only as a control mechanism but also as a strategic tool to support the sustainable growth and long-term competitiveness of village-owned enterprises in Indonesia.